What is ethnographic about digital ethnography? A sociological perspective - Forberg, Peter; Schilt, Kristen (Frontiers in Sociology, 2023)
When COVID-19 health guidelines vastly restricted or shut down in-person ethnographic research at U.S. universities in 2020, many researchers pivoted to forms of online qualitative research using platforms such as WeChat, Twitter, and Discord. This growing body of “small data” internet research in sociology is often encapsulated under the umbrella term “digital ethnography.” But the question of what makes digital qualitative research ethnographic remains open. In this article, we posit that digital ethnographic research, in keeping with traditional approaches to ethnography, necessitates a negotiation of the ethnographer’s self-presentation and co-presence within the field that other forms of qualitative research, such as discourse analysis, do not require to satisfy their epistemological stance. To make our case, we provide a brief overview of qualitative digital research in sociology and related disciplines. Then, we draw upon our experiences conducting ethnographies in-person and online to explore how decisions about self-presentation and co-presence facilitate or block the generation of meaningful ethnographic data. We think through pertinent questions such as: Does the lower barrier for anonymity online justify disguised research? Does anonymity generate “thicker” data? How should digital ethnographers participate in research environments? What are the possible repercussions of digital participation? We demonstrate that the affordances of the internet create new research strategies but that the resulting ethical dilemmas are familiar to "in-person" ethnographic theory. We argue that an ethnographer’s decisions about ethnographic presence should be sensitive to digital and social contexts in order to produce meaningful ethnographic data. We conclude with actionable takeaways for ethnographers interested in working in digital spaces.